2016
DOI: 10.3390/su8111146
|View full text |Cite
|
Sign up to set email alerts
|

Human Impact on Vegetation Dynamics around Lhasa, Southern Tibetan Plateau, China

Abstract: Abstract:Human impact plays an increasing role on vegetation change even on the Tibetan Plateau, an area that is commonly regarded as an ideal place to study climate change. We evaluate the nature and extent of human impact on vegetation dynamics by the comparison of two areas: the relative highly populated Lhasa area and a nearby less populated Lhari County. Our results indicate that human impact has mainly decreased vegetation greenness within 20 km of the urban area and major constructions during 1999-2013.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 36 publications
(43 reference statements)
2
33
0
Order By: Relevance
“…Relationships between NDVI and other variables are generally examined via a correlation analysis [17,20,22,34,40]. In this study, the linear regression analysis was undertaken between mean annual G-NDVI and climate factors (G-P, G-T) to explain the spatial variabilities of G-NDVI.…”
Section: Analyzing the Sensitivity Of G-ndvi To Climate Changementioning
confidence: 99%
See 2 more Smart Citations
“…Relationships between NDVI and other variables are generally examined via a correlation analysis [17,20,22,34,40]. In this study, the linear regression analysis was undertaken between mean annual G-NDVI and climate factors (G-P, G-T) to explain the spatial variabilities of G-NDVI.…”
Section: Analyzing the Sensitivity Of G-ndvi To Climate Changementioning
confidence: 99%
“…In cities, urbanization may be the crucial driver of effects on vegetation cover change and can be greater than climate factors [20,34] and hence mask the climate effects. For instance, urban land expansion, driven by urbanization in cities, could directly transform a large amount of agricultural lands to urban lands [43,44,47].…”
Section: Driving Forces Of the Temporal Variability Of G-ndvimentioning
confidence: 99%
See 1 more Smart Citation
“…These vegetation fragments in São Paulo City are managed locally and designated as areas for leisure and sports, as well as biodiversity conservation. Like larger forest fragments, these areas are subjected to such stresses as fire, pollution, urban growth and even vandalism [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, significant relationships between NDVI and indicators of climate have been used to demonstrate that vegetation changes are closely related to variations in the latter [5,11]. Temperature and precipitation are the most significant factors influencing changes in the NDVI [13]; trends in this index in northern mid and high latitudes are controlled by increasing temperature while fluctuations in the semi-arid regions of the Southern Hemisphere are due to decreasing precipitation [5]. Precipitation is known to be more important than temperature as a climatic variable influencing changes in vegetation cover in arid and semi-arid regions [2,9,14], and it has also been suggested that the relationship between the NDVI and temperature is more marked than that between this index and precipitation in temperate monsoonal climate regions [15].…”
Section: Introductionmentioning
confidence: 99%